Cohesiveness as moderator of organizational citizenship behaviour and turnover intention relationship a proposition / Shaiful Annuar Khalid and Norshimah Abdul Rahman - Khalid, Shaiful Annuar; Abdul Rahman, Norshimah (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
Employee behaviors that exceed formal job duties such as helping coworkers, displaying willingness to bear inconveniences at workplace, involving actively in organization’s development are examples of behaviours that are critical to organizations’ achievement (Katz & Kahn, 1978). Organ (1988) labeled these be haviors as organizational citizenship behaviors (OCB) and defines it as “individual behavior that is discretionary, not directly or explicitly recognized by the formal reward system, and that in the aggregate promotes the effective functioning of the organ ization". These human behaviours have received extensive attention by researchers in recent years. Despite the hypothesis that OCB contributes to organizational effectiveness (Organ, 1988; Podsakoff et al., 2000), previous research had concentrated more o n identifying factors affecting OCB and less research focus had been given to investigating its consequences. The lacking of research investigating the consequences of OCB representing one of the gaps in current OCB literature. It is important to study fac tors that contribute to OCB so that organizations can take appropriate actions to promote OCB among employees. Nevertheless, more empirical evidences are needed regarding the effects of the OCB so that the investment and actions taken by organizations in p romoting OCB is meaningful and justify.